MENINGKATKAN KEMAMPUAN MEMAHAMI KONSEP BILANGAN MELALUI PERMAINAN LOMPAT GAMBAR BAGI ANAK TUNAGRAHITA RINGAN (Single Subject Research Kelas D1/C di SLB Muhammadiyah IX Pauh Padang) - Amanda - Sartika (Jurnal Penelitian Pendidikan Khusus, 2013)
This research of background overshadow by problems which researcher find in SLB Muhammadiyah Pauh IX Padang, a child of handicap light  class I semester of I finding difficulties in comprehending number concept 1-10. Matter is proven, when conducting and interview of asesmen to child in the reality a child only can mention and show number one. To overcome this problems researcher try to give alternative by using jump picture game assumed can assist handicap in improve repairing number concept 1-10. This research aim to  increase ability comprehend number concept to child of handicap light through jump picture game. Research type is Single Subject Research (SSR) that is research which in doing a condition differ to use A-B desain. Condition of A is baseline namely the condition of early ability of child in comprehending number concept before in giving action. While condition of B represent the condition of intervention namely the condition of where child in giving intervention through jump picture game. Goals size measure of behavior seen from how much gratuity persentage of child show and mention number 1-10. Result of this research seen that ability comprehend number concept to child of handicap  light in  SLB Muhammadiyah Pauh IX Padang mount after in giving jump picture game. This proven matter when perception performed within two session that is  first of session of baseline before given by intervention (A) which is donethe six of perception times rill, and percentage of ability comprehend number concept at this condition lay in to span 0%, 0%, 0%, 10%, 10% and 10%. Second intervention sesion (B) by using jump picture game, perception conducted by counted compassion multiply perception, and percentage of ability comprehend number concept to child of handicap at this condition lay in to span 10%, 10%, 20%, 30%, 30%, 40%, 30%, 40%, 40%, 50%, 50%, 60%, 60%, 50%, 70%, 80%, 80% and 80%. Pursuant to result of this research can mean that ability comprehend number concept to child of handicap light of class D1 / C in SLB Muhammadiyah Pauh IX Padang mount to through jump picture game as well as can be suggested to old fellow, headmaster and teacher that game jump picture can be used as by study method in improving ability comprehend number concept to child of handicap light.